Rapid 3D Printing of Electrohydraulic (HASEL) Tentacle Actuators. (18th August 2020) - O'Neill, Maura R.; Acome, Eric; Bakarich, Shannon; Mitchell, Shane K.; Timko, Julia; Keplinger, Christoph; Shepherd, Robert F.
Abstract: A comprehensive material system is introduced for the additive manufacturing of electrohydraulic (HASEL) tentacle actuators. This material system consists of a photo‐curable, elastomeric silicone‐urethane with relatively strong dielectric properties (εr  ≈ 8.8 at 1 kHz) in combination with ionically‐conductive hydrogel and silver paint electrodes that displace a vegetable‐based liquid dielectric under the application of an electric field. The electronic properties of the silicone material as well as the mechanical properties of the constitutive silicone and hydrogel materials are investigated. The hydraulic pressure exerted on the dielectric working fluid in these capacitive actuators is measured in order to characterize their quasi‐static behavior. Various design features enabled by 3D printing influence this behavior—decreasing the voltage at which actuation begins or increasing the force density in the system. Using a capacitance change of >35% across the actuators while powered, a demonstration of self‐sensing inherent to HASELs is shown. Antagonistic pairs of the 3D printed actuators are shown to exert a blocked force of over 400 mN. An electrohydraulic tentacle actuator is then fabricated to demonstrate the use of this material and actuation system in a synthetic hydrostat. This tentacle actuator is shown to achieve motion in a multi‐dimensional space. Abstract : A comprehensive multimaterial system and fabrication route for the design and manufacture of soft tentacles is introduced. 3D printing enables the patterning of dense arrays of capacitive actuators to form a synthetic muscular hydrostat capable of multidimensional motion. The actuation and self‐sensing capabilities of the capacitive modules are demonstrated.